Implementation of a Web-Based Academic and Non-Academic Achievement Information System at the Student Affairs and Alumni Office of Universitas Muhammadiyah Sumatera Utara Using the Rapid Application Development (RAD) Method - Ravindra Singh Dhillon (Al'Adzkiya, 2024)
This research discusses the implementation of a web-based academic and non-academic achievement information system at the Student Affairs and Alumni Office of Universitas Muhammadiyah Sumatera Utara. The system is designed to address issues in managing student achievement data, which was previously handled manually, often resulting in data inaccuracies, delayed reporting, and a lack of convenience in accurately monitoring student achievements. Using the Rapid Application Development (RAD) methodology, the system development is conducted quickly and iteratively through planning, design, and prototype construction phases that allow users to test it directly. RAD was chosen because it enables results that meet user needs in a relatively short time and facilitates adjustments throughout the development process. This information system allows the student affairs office to record, process, and report student achievement data more efficiently. Additionally, the system includes features for searching and tracking achievements, assisting the university in analyzing and evaluating student accomplishments in both academic and non-academic areas. The results of this research show that the developed system can provide accurate, real-time data and contributes to the improvement of service quality at the Student Affairs and Alumni Office. It is expected that this system will enable more transparent, effective student achievement data management and support the enhancement of graduate quality.